Antecedents and Consequences of Entrepreneurial Leadership Behaviour in Southeast Minahasa District Government - Kula, Agustince Neti; Lapian, Stanss Levynna Hermien Verronica Joyce; Tumbel, Altje Lenny; Budiarso, Novi Swandari (AIBPM Publisher, 2021)
The main purpose of this research is to analyse Theory of Planned Behaviour (TPB), bureaucracy culture, Entrepreneurial Leadership Behaviour /ELB, and the performance of government apparatus in Southeast Minahasa District. The design of the data was obtained from 86 respondents who work as the government apparatus in Southeast Minahasa. Data analysis in this study used an alternative method of Structural Equation Modelling (SEM). The findings of the research showed that attitude and perceived behavioural control have significant influence on IEL, and subjective norm does not have significant influence on IEL. The authority has significant influence, but also weak on performance of Government Officials. ELB has the highest contribution for the performance of Government Officials. It means that Entrepreneurial Leadership Behaviour is the answer for public demand for creating a good government.